2016
DOI: 10.1007/s13312-016-0970-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation for treatment and prevention of pneumonia in under-five children: A randomized double-blind placebo controlled trial

Abstract: There is no robust evidence of a definite biological benefit, either for therapy or prevention, to suggest a routine megadose supplement of vitamin D3 for under-five children with severe pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
109
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(116 citation statements)
references
References 20 publications
2
109
0
5
Order By: Relevance
“…Peak concentrations of 25(OH)D were found 3 days after bolus administration, which is longer than the time taken for resolution of the clinical features of severe pneumonia (median approximately 30 hours). The findings of Gupta, et al [5] are in keeping with two other studies which reported a lack of a therapeutic effect of acute vitamin D supplementation on the rate of resolution of acute pneumonia [7]. The second aspect of the study by Gupta, et al [5] was to assess the effect of vitamin D supplementation on the incidence of recurrence of pneumonia over six months.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…Peak concentrations of 25(OH)D were found 3 days after bolus administration, which is longer than the time taken for resolution of the clinical features of severe pneumonia (median approximately 30 hours). The findings of Gupta, et al [5] are in keeping with two other studies which reported a lack of a therapeutic effect of acute vitamin D supplementation on the rate of resolution of acute pneumonia [7]. The second aspect of the study by Gupta, et al [5] was to assess the effect of vitamin D supplementation on the incidence of recurrence of pneumonia over six months.…”
supporting
confidence: 62%
“…The findings of Gupta, et al [5] are in keeping with two other studies which reported a lack of a therapeutic effect of acute vitamin D supplementation on the rate of resolution of acute pneumonia [7]. The second aspect of the study by Gupta, et al [5] was to assess the effect of vitamin D supplementation on the incidence of recurrence of pneumonia over six months. Once again, no effect was noted, but it is possible that the bolus of vitamin D was not given frequently enough to maintain vitamin D sufficiency, as the difference in 25(OH)D in the treatment group between admission and 3 months had fallen to only 7 ng/mL compared to 30 ng/mL at two weeks.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…The completed trials were from India [23] [24] and Afghanistan [25] . These trials enrolled children of different age groups, severity of pneumonia, and varied in terms of the dosage and duration of vitamin D supplementation.…”
Section: Characteristics Of the Included Rctsmentioning
confidence: 99%